2019
DOI: 10.29333/iji.2019.12184a
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Application of Electronic Portfolio on Undergraduate English Majors’ Writing Proficiency and their Self-Regulated Learning

Abstract: The role of technology in educational settings all around the world has changed the methods of teaching and assessment in the last few decades. Unfortunately, the shortcomings of e-learning in Iran have deprived students of many advantages of it. This research paper tries to answer the questions regarding the effect of e-portfolio on the students' writing proficiency in the context of learning English as a foreign language and the learners' use of self-regulated learning strategies. Furthermore, the attitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
(17 reference statements)
2
16
0
Order By: Relevance
“…Besides, the students found that an e-portfolio is helpful to improve their ability to learn English. These findings are in line with Barrot (2015) and Karami et al (2019), elaborating that a portfolio helps the students to develop their performance in writing, develop the teachers' roles, support learning, encourage students' participation, enhance the testing process, improve students' autonomous learning, and maintain lifetime learning.…”
Section: Findings and Discussionsupporting
confidence: 79%
“…Besides, the students found that an e-portfolio is helpful to improve their ability to learn English. These findings are in line with Barrot (2015) and Karami et al (2019), elaborating that a portfolio helps the students to develop their performance in writing, develop the teachers' roles, support learning, encourage students' participation, enhance the testing process, improve students' autonomous learning, and maintain lifetime learning.…”
Section: Findings and Discussionsupporting
confidence: 79%
“…It had a significant impact on promoting different teaching practices, self-efficacy and language skills. Results of this are in line with most of studies in literature (Karami et al, 2019, Almusharraf, 2019and Slepcevic-Zach & Stock, 2018, Cheng & Chau, 2013. The study addressed a very vital issue i.e.…”
Section: Discussionsupporting
confidence: 89%
“…The first implication is that teachers of writing are strongly recommended to integrate technology effectively with their methods of teaching. Integrating technology into teaching methodologies will not only increase the learners’ motivation but also promote the teaching process, in general (Karami et al , 2019; Wihastyanang et al , 2020). Therefore, instructors of writing have to design activities in which learners can get benefits from their passion for technology in improving their abilities to write.…”
Section: Discussionmentioning
confidence: 99%
“…As learning writing is a principal component of language learning, technological devices have a crucial role in both English as a Foreign Language (EFL) and English as a Second language (ESL) writing training, especially in the past 20 years. In recent research studies, writing and technology are increasingly paired and the role of technology in improving writing is widely investigated (Alharbi, 2019; Barrot, 2020; Iwasaki et al , 2019; Karami et al , 2019; Kessler, 2020; Pearson et al , 2005; Tam, 2012; Wihastyanang et al , 2020). A considerable amount of studies have been published on the effect of computers and their different applications on the development of learners’ writing abilities (Abdul Fattah, 2015; Ahmed, 2015; Ahmed, 2013; Bikowski and Vithanage, 2016; Janfaza et al , 2014; Kashani et al , 2013; Khalil, 2017; Khoshsima and Sayadi, 2016; Lam et al , 2018).…”
Section: Introductionmentioning
confidence: 99%